2011
DOI: 10.1136/bjsm.2010.075879
|View full text |Cite
|
Sign up to set email alerts
|

A report of the medical team activity at the 2009 Special Olympics GB

Abstract: A large multisport event for athletes with learning disabilities carries a significant medical workload that has not been studied previously, with different sports having different individual risks and demands. The vast majority of consultations are for systemically well athletes that can be managed locally without necessity for hospital admission. This study identifies the quantity and nature of medical consultations undertaken during this event in an attempt to inform planning for future events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Analysis of the specific injuries and illnesses has previously been published and the data standardised to show the number of consultations per 1000 athlete hours at each individual sporting event 6. This will enable comparison against other sports injury data that does not involve people with a learning disability.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the specific injuries and illnesses has previously been published and the data standardised to show the number of consultations per 1000 athlete hours at each individual sporting event 6. This will enable comparison against other sports injury data that does not involve people with a learning disability.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, athletes with intellectual disability have been shown to have poor PB compared to those without intellectual disability (Dellavia et al, 2009). Despite the benefits of sports practice for these individuals (Jouira et al, 2021; Jouira et al, 2022; Pineda et al, 2023), it is also accompanied by an inherent risk for injury (Wheeler et al, 2012; White et al, 2018). Intellectual disability is illustrated by an intellectual quotient (IQ) below 70 (Boat et al, 2015) that classifies the severity degree into mild, moderate, severe or profound intellectual disability.…”
Section: Introductionmentioning
confidence: 99%
“…The ICF categorises intellectual disability based on deficits in intellectual and adaptive functioning (WHO, 2001), emphasising the need for careful monitoring and assessment to ensure sport safety. This imperative is underscored by documented higher injury rates, increased injury mortality, and morbidity rates in individuals with intellectual disability compared to those with typical development (Wheeler et al, 2012; White et al, 2018). Continuous monitoring and assessment are therefore essential, aligning with the broader goal of promoting the overall well‐being and inclusivity of individuals with intellectual disability, including their participation in sports activities.…”
Section: Introductionmentioning
confidence: 99%
“…The medical workload from the 2009 SO Great Britain was studied, and it was identified that each event has different individual risks and medical needs, with most consultations for well-athletes managed locally without hospitalization. 5 Study of podiatric conditions in 2011 SO World Summer Games athletes in Greece found that SO athletes have a greater prevalence of podiatric structural conditions than the general population. 6 Finally, a report of medical planning for a large SO event (World Games Los Angeles 2015) had focused on logistical considerations within US events but did not analyze injury data in athletes.…”
Section: Introductionmentioning
confidence: 99%